Qur'an Center: a Key Pillar in Strengthening Islamic Education in Modern Society - Azmi, Muhammad Fadhli; Mahariah, Mahariah (Institut Agama Islam An-Nawawi Purworejo, 2025)
This research analyzes the contribution of Qur'an Center in instilling the values ​​of Islamic education based on the Qur'an, as well as its relevance to the concept of Islamic education in Surah Luqman verses 13-19. The Qur'an Center has an important role in shaping the character of the younger generation, especially amidst the negative impacts of globalization which can shift religious values. This research uses a qualitative approach with descriptive analysis, collecting data through observation, interviews and document analysis. The findings show that Qur'an Center Amal Ikhlash has implemented guidance based on Al-Qur'an values ​​well, but the implementation is not yet completely comprehensive. Several values ​​in Surah Luqman verses 13-19 have been integrated into the curriculum, but there is still room for development. Qur'an Center plays an important role in instilling the values ​​of Islamic education which can shape the character and personality of students who are strong, and able to compete in the era of globalization. This research provides important insights for Islamic educational institutions to strengthen Al-Qur'an-based curricula. In addition, this research offers a new approach by integrating the concept of Islamic education from Surah Luqman as an innovation in strengthening character education that is relevant to the challenges of the modern era.